Incidence, management, and reporting of severe and fatal Plasmodium falciparum malaria in secondary and tertiary health facilities of Alipurduar, India in 2009 - Jagannath Sarkar , Naman K. Shah & Manoj V. Murhekar (Journal of Vector Borne Diseases, 2012)
Background & objectives: The proportion of malaria cases that are complicated and fatal are not well describedin India. Alipurduar sub-division of Jalpaiguri district in West Bengal is highly endemic for malaria. We constructeda retrospective cohort of severe malaria patients admitted in the secondary and tertiary care facilities in Alipurduarto determine the incidence, assess the management, and evaluate the reporting of severe and fatal malaria.Methods: We reviewed routine surveillance data and the case records of all the malaria patients admitted in allsecondary and tertiary care facilities, both public and private. We defined severe malaria cases as Plasmodiumfalciparum infection with clinical signs and symptoms of organ involvement in a resident of Alipurduar admittedduring January to December 2009. We compared clinical and demographic characteristics of severe malariacases that died with those who survived. We also reviewed human resources and laboratory facilities availablefor the treatment of severe malaria in these health facilities.Results: During 2009, 6191 cases of P. falciparum in Alipurduar were reported to the malaria surveillancesystem. We identified 336 (5.4%) cases of severe malaria among which 33 (9.8%) patients died. Four malariadeaths were also recorded from primary health centres. Only 17 of the 37 (46%) total deaths recorded werereported to the routine surveillance system. Most severe cases were males (65%), aged >15 years (72%), andnearly half were admitted to secondary care hospitals (48%). In multivariate analysis, the risk factors associatedwith death included increased delay fever onset and hospitalization, treatment in a secondary level hospital,younger age, and multi-organ involvement. The secondary level public hospital had too few physicians andnurses for supporting severe malaria patients as well as inadequate laboratory facilities for monitoring suchpatients.Conclusions: Severe and fatal malaria continue to burden Alipurduar and record keeping in health facilities waspoor. Many malaria deaths were not routinely reported even in the public sector. Improved surveillance andincreased human and laboratory resources are needed to reduce malaria mortality